Immunohistochemical determination of the site of antidepressant-like effects of glucagon-like peptide-2 in ACTH-treated mice. (21st May 2015) - Sasaki-Hamada, S.; Yuri, Y.; Hoshi, M.; Oka, J.-I.
Highlights: Chronic GLP-2 administrations induced Fos -IR in the DMH. GLP-2 induced Fos -IR of hypothalamic GABAergic neuron in ACTH-treated mice. GLP-2 induced Fos -IR of hypothalamic CRF-containing neurons in ACTH-treated mice. GLP-2 affected hippocampal neurogenesis in ACTH-treated mice. Abstract: The intracerebroventicular administration (i.c.v.) of glucagon-like peptide-2 (GLP-2) had antidepressant-like effects on saline-treated mice in the forced-swim test. The GLP-2 treatment (3 μg, i.c.v.) for 6 days, but not that of imipramine had antidepressant-like effects on adrenocorticotropic hormone (ACTH)-treated mice. The immunohistochemical detection of the c-fos protein ( Fos ) revealed that the administration of GLP-2 induced Fos -immunoreactivity ( Fos -IR) in the dorsomedial hypothalamic nucleus in saline-treated and ACTH-treated mice, and also in the hippocampal dentate gyrus in ACTH-treated mice, but not in saline-treated mice. In contrast, Fos -IR in the paraventricular nucleus of the hypothalamus decreased after the administration of GLP-2 to ACTH-treated mice. In ACTH-treated mice, the chronic administration of GLP-2 affected hippocampal neurogenesis, in addition to Fos -IR in hypothalamic GABAergic neurons and corticotrophin-releasing factor-containing neurons. These results suggest that GLP-2 acts on specific brain regions to regulate stress conditions, and induces antidepressant-like effects under imipramine-resistant conditions, which may be associated with the modulation of the hypothalamic–pituitary–adrenal-axis.